Evaluation of Extreme Thermal Processing Methods to Improve Nutrient Utilization of Low-Energy Diets for Finishing Pigs - G. E. Bokelman; K. F. Coble; C. R. Stark; J. C. Woodworth; M. D. Tokach; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 270 pigs (PIC 337 × 1050; initially 115.7 lb) were used in a 79-d experiment to determine the effects of long-term conditioning or extrusion on finishing pig nutrient digestibility, growth performance, and carcass characteristics. There were 7 or 8 pigs per pen and 9 pens per treatment. Treatments included the same basal diet processed as: 1) nonprocessed mash; 2) pelleted with 45-s conditioner retention time; 3) pelleted with 90-s conditioner retention time; or 4) extruded. Diets were fed in three phases with the same low-energy diet formulation fed across treatments, containing 30% corn dried distillers grains with solubles and 19% wheat middlings. Pigs fed thermally processed feed, regardless of method, had improved ADG, F/G, ether extract, and crude fiber apparent total tract digestibility (P<0.05) compared to those fed the mash diet, but thermal processing did not affect ADFI . Extruded diets tended to improve F/G compared to pelleted diets (P = 0.09). Pigs fed any thermally processed treatment had greater HCW compared to those fed mash (P<0.05). Improvements in fat and crude fiber digestibility (P<0.05) led to improved caloric efficiency in pigs fed thermally processed diets. Thermal processing did not influence percentage yield, backfat, or loin depth when HCW was used as a covariate. However, pigs fed thermally processed diets had greater jowl fat iodine value compared to those fed mash diets (P<0.05). Electrical energy usage during thermal processing was recorded. Pigs fed mash diets had greater (P<0.05) cost per lb of gain, as well as reduced gain value and income over feed costs, compared to those fed thermally processed diets. This experiment confirms the benefits of thermally processing feeds to improve ADG and F/G, but compromises carcass fat iodine value. Additionally, this research suggests that more extreme thermal processing conditions may be used without hindering nutrient utilization.
Keywords: carcass fat quality; extrude; pellet; performance; pig